Analisis Persiapan Indonesia dalam Menerapkan Key Audit Matters - Joben Emilio; Melisa Kurniani; Wedi Yanto (STIE AMKOP, 2022)
Abstract This study aims to determine the analysis of Indonesia's preparation in implementing the key audit matters. This research is focused on the enactment of a new accounting standard, namely accounting standard 701 in Indonesia. This research was conducted in analyzing the exposure draft issued by IAPI in 2021 concerning